Perception of digital competencies in second cycle of secondary level teachers in the Dominican Republic, 2022-2023 - Batista-Pérez, Deybis Ramón (2023)
Objective. To reveal the perception of digital competences presented by the teachers of the second cycle of secondary level in an educational center in the Dominican Republic, as perceived by the students who study or have studied in the center under study, in the implementation of virtual education post-COVID-19 for the period 2022-2023, as a result of the passage from classroom to virtual training in a massive way in an area with many limitations in internet connection and with a high precariousness. Methods. A quantitative approach methodology and descriptive scope were used toknow the answers of the students, through the application of a digital survey with closed and multiple-choice questions. Results. The inadequate use of information and communication technologies in the teaching-learning processes is highlighted, as well as the low use of these educational tools. Conclusions. It is shown that teachers are not trained or prepared for virtual education, and that teachers and students do not know how ICTs are implemented